Innovative trends and strategies for the integral valorization of products in the beer supply chain - N. Barbagallo, Riccardo; A.C. Rutigliano, Chiara; Rizzo, Valeria; Muratore, Giuseppe (Italian Journal of Food Science, 2024)
This review aims to explore the latest innovations in beer supply chain. Innovation is defined as the combined application of strategies that enhance intrinsic and extrinsic product characteristics while optimizing complementary aspects for a modern approach to the food market. The study is structured around key themes that define the overall quality of beer supply chain: safety (wholesomeness and authenticity), biological quality (chemical composition, sensory profile, and nutritional quality), process quality, convenience, and commodities. The goal is to promote accurate dissemination of information within the beer community and dispel common misconceptions. These misconceptions often arise from flawed approaches, leading to the creation of urban legends and unfounded prejudices. Special attention is given to innovation and research in the craft beer sector, which is rapidly growing in Italy and the global market.